2007
DOI: 10.2113/gselements.3.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Re-equilibration of Zircon in Aqueous Fluids and Melts

Abstract: Natural zircon crystals often show complex secondary textures that cut across primary growth zones. In zircon showing structural damage caused by self-irradiation, such textures are the result of a diffusion- reaction process in which a hydrous species diffuses inwards and “catalyzes” structural recovery. Nanoscale pores develop, solvent elements such as Ca, Al and Fe are gained, and radiogenic Pb is lost. In both aqueous fluids and melts, replacement of zircon with undamaged structure by a coupled dissolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
360
2
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 710 publications
(420 citation statements)
references
References 30 publications
22
360
2
13
Order By: Relevance
“…Some published illite crystallinity data from the middle Ecca Group support lowgrade metamorphic temperatures of 170-200°C (Hälbich et al, 1983), which is within range of when fluid-mediated lattice damage initiates in zircon (Geisler et al, 2002;Geisler et al, 2007). However, we did not find any clear evidence for reabsorption or alteration of the oscillatory zoning in the zircons (Fig.…”
Section: Shrimp U-pb Geochronologysupporting
confidence: 51%
“…Some published illite crystallinity data from the middle Ecca Group support lowgrade metamorphic temperatures of 170-200°C (Hälbich et al, 1983), which is within range of when fluid-mediated lattice damage initiates in zircon (Geisler et al, 2002;Geisler et al, 2007). However, we did not find any clear evidence for reabsorption or alteration of the oscillatory zoning in the zircons (Fig.…”
Section: Shrimp U-pb Geochronologysupporting
confidence: 51%
“…The detailed study of Geisler et al (2007) inferred a diffusion-limited dissolutionrecrystallization process along a reaction front as a cause for disequilibrium during zircon growth, which strikingly resembles the patchy-zoning texture observed in the MC zircons. This process is dynamic and occurs along inwardmoving interfaces (e.g.…”
Section: Discussionmentioning
confidence: 66%
“…2c, 3a) may represent channels along which dissolution and recrystallization took place. It is inferred that dissolution and recrystallization occurred simultaneously (Geisler et al, 2007), as suggested by evidence of inward replacement (Fig. 2a, e) along porous zircon.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations